The cat who saved the library : a novel - Natsukawa, Sōsuke, 1978- (Cat who, 2025)
"A chronic asthma condition prevents thirteen-year-old Nanami from playing sports or spending time with her friends after school. But nothing can stop her from one of her favorite activities. Nanami loves to read and happily spends much of her free time in the library, cocooned among the stacks. Then one day, Nanami notices that, despite the library being as deserted as ever, some of her favorite books...are disappearing from the shelves. When she alerts the library staff, they dismiss her concerns...That's when Tiger, the talking tabby cat who saves books, comes to the rescue. Are Nanami and Tiger prepared to face the dangerous challenges that lie ahead? Why are faceless gray soldiers burning books in a stone castle?"--